Synthesis and Applications of Copper-Based Catalysts (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Copper-based catalysts possess important applications in diverse reactions and have received considerable attention from material and catalysis researchers. A great challenge in this field is the facile synthesis of copper-based catalysts with enhanced catalytic activity, selectivity, and durability. This Special Issue of Catalysts, entitled “Synthesis and Applications of Copper-based Catalysts”, presents state-of-the-art synthetic strategies for copper-based catalysts, as well as information on their structure and catalytic use in heterogeneous and homogeneous catalysis, which is helpful for developing novel high-efficiency Cu-based catalysts and synthetic methodology, and for exploring their new catalytic applications.